(untitled) (Research, Society and Development, 2021)
Malnutrition has been very common in children and adolescents undergoing cancer treatments. It is a disease caused by a lack of nutrients, generating a deficit and causing a series of damages to the body, which can even lead to death if left untreated. Due to its adverse effects, nutrition, with nutritional therapy, has a very important role in maintaining and improving the nutritional status of these patients. The main objective of this study was to raise awareness about the incidence of malnutrition in cancer patients and the importance of nutritional therapy at that time. This was an observational, cross-sectional descriptive study. Data collection was carried out through the application of an online questionnaire with parents or guardians of children and/or adolescents aged 7 to 19 years, where information was obtained such as anthropometric data, type of treatment in progress and the symptoms presented. This information resulted in a prevalence of neoplasms in the male population, with a mean age of 12.5 years, patients, mostly undergoing chemotherapy and radiotherapy. There was considerable weight loss, in 92.9% of the research participants, due to the various gastrointestinal and oral symptoms presented and with this, the importance of nutritional therapy in this treatment was realized, in order to minimize the decline in the nutritional status of the patient.